Insights into ROS‐dependent signalling underlying transcriptomic plant responses to the herbicide 2,4‐D - Romero Puertas, María C.; Peláez-Vico, María Ángeles; Pazmiño, Diana M.; Rodríguez Serrano, María; Terrón Camero, Laura; Bautista-Moreno, Rocío; Gómez-Cadenas, Aurelio; Claros-Díaz, Manuel Gonzalo; León, José; Sandalio, Luisa M. (Plant Cell & Environment, 2022)
The synthetic auxin 2,4-dichlorophenoxyacetic acid (2,4-D) functions as an agronomic weed control herbicide. High concentrations of 2,4-D induce plant growth defects, particularly leaf epinasty and stem curvature. Although the 2,4-D triggered reactive oxygen species (ROS) production, little is known about its signalling. In this study, by using a null mutant in peroxisomal acyl CoA oxidase 1 (acx1-2), we identified acyl-coenzyme A oxidase 1 (ACX1) as one of the main sources of ROS production and, in part, also causing the epinastic phenotype following 2,4-D application. Transcriptomic analyses of wild type (WT) plants after treatment with 2,4-D revealed a ROS-related peroxisomal footprint in early plant responses, while other organelles, such as mitochondria and chloroplasts, are involved in later responses. Interestingly, a group of 2,4-D-responsive ACX1-dependent transcripts previously associated with epinasty is related to auxin biosynthesis, metabolism, and signalling. We found that the auxin receptor auxin signalling F-box 3 (AFB3), a component of Skp, Cullin, F-box containing complex (SCF) (ASK-cullin-F-box) E3 ubiquitin ligase complexes, which mediates auxin/indole acetic acid (AUX/IAA) degradation by the 26S proteasome, acts downstream of ACX1 and is involved in the epinastic phenotype induced by 2,4-D. We also found that protein degradation associated with ubiquitin E3-RING and E3-SCF-FBOX in ACX1-dependent signalling in plant responses to 2,4-D is significantly regulated over longer treatment periods.
Keywords: Auxina; Acyl‐CoA oxidase; Auxin; Peroxisomes; Reactive oxygen species; Transcriptome